2021
DOI: 10.2298/sarh210608090b
|View full text |Cite
|
Sign up to set email alerts
|

High-dose-rate endobronchial brachytherapy in the management of advanced lung cancer - comparison according to the presence of lung atelectasis

Abstract: Introduction/Objective. Locally advanced lung cancer (LC) is often accompanied with atelectasis of either a part or the entire lung. The aim of this study was to establish the benefits of brachytherapy on the patients? quality of life (QoL), the length of the progression free survival (PFS), and the overall survival (OS) as related to the presence or absence of atelectasis after the applied treatment. Methods. The total of 100 patients with locally advanced LC or endobronchial metastasis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Brachytherapy represents a palliative procedure in LC where there is obstruction of the main airways by a tumor and is often used with other interventional therapeutic procedures, all to rapidly improve the Quality of Life (QoL) [ 38 ]. The effects of brachytherapy are significant because patients can have an improvement in QoL in a few hours or days after the applied procedure, and in most cases, brachytherapy has a palliative therapeutic goal in the advanced stage of the disease [ 13 , 39 ]. In our study, an improvement in the patient’s ECOG status was demonstrated for both types of applied brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachytherapy represents a palliative procedure in LC where there is obstruction of the main airways by a tumor and is often used with other interventional therapeutic procedures, all to rapidly improve the Quality of Life (QoL) [ 38 ]. The effects of brachytherapy are significant because patients can have an improvement in QoL in a few hours or days after the applied procedure, and in most cases, brachytherapy has a palliative therapeutic goal in the advanced stage of the disease [ 13 , 39 ]. In our study, an improvement in the patient’s ECOG status was demonstrated for both types of applied brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In curative brachytherapy, the radiation field is defined as a three-step process: the macroscopic tumor lesion is defined by diagnostic methods and is designated as the gross tumor volume (GTV), the clinical radiation field is designated as the clinical target volume (CTV), and finally, the planning target volume (PTV) is estimated 1 cm over and 1 cm under the CTV due to the accuracy of localization and the possible movement of the patient during transport. In this way, the tumor, the bronchial catheter position, and the OAR are visualized [ 12 , 13 , 14 ]. The most frequently applied dose regimens are 2 × 7 Gy; 2 × 7.2 Gy and 1 × 15 Gy.…”
Section: Introductionmentioning
confidence: 99%